Humanizing education through consumerism advocacy and vegetable garden project - Zainudin, Dolhadi; Mhd. Sarif, Suhaimi; Yahya, Rohaziah (Kulliyyah of Economics and Management Sciences IIUM, 2021)
Humanizing education with maqasid al-shariah and sustainability agenda can be done in edu-action activities through consumerism advocacy and vegetable garden project. Prior to the activities, there is a need to get insights and tips on how to initiate and manage activities. Activities with a good guidance can produce high impact into human civilization and sustainability. This chapter deliberates the humanizing education experience through consumerism advocacy and vegetable garden. The outcome of the activities is very meaningful to reflect humanizing education.